A Note on the Large Deviation Principle for Discrete Associated Random Variables. (6th January 2015) - Matuła, Przemysław; Ziemba, Maciej
Abstract : We present sufficient conditions under which the sequence of arithmetic means S n / n, where S n = X 1 + ⋯ + X n, is the partial sum built on a stationary sequence X n n ≥ 1 of associated integer-valued and uniformly bounded random variables, which satisfy the large deviation principle.